Eosinophilic Gastroenteritis: An Unusual Disease of Gastrointestinal Tract - Gaudêncio, Margarida; Mendonça, Teresa (Gazeta Médica, 2022)
Eosinophilic gastroenteritis (EGE) is a rare gastrointestinal disease characterized by generalized abdominal pain, nausea, vomiting, diarrhea, gastrointestinal bleeding and weight loss. The etiology and pathogenesis are not well understood and mostly based on case reports. Clinical presentation may vary depending on sites and depth of involvement of the gastrointestinal tract. The diagnosis is usually confirmed by histology that shows eosinophilic infiltration and the absence of secondary cause of eosinophilia. The authors present a case report of a 47-year-old woman that was diagnosed with dyslipidemia, obesity and allergic rhinitis. She had no significant family history. She was admitted in internal medicine department with 2 weeks of abdominal pain, nausea, vomiting, diarrhea and weight loss (> 10%). Further study revealed increased eosinophil count, normocytic anemia, elevated erythrocyte sedimentation rate and normal Ig E levels. Digestive endoscopic study was performed, and multiple biopsy specimens showed moderate eosinophilic infiltration in stomach and duodenal mucosa. The patient was started on prednisolone, with clinical improvement. Follow-up go the patient twenty years after the beginning of this treatment showed stabilization of clinical symptoms and laboratory tests. So, eosinophilic gastroenteritis is characterized by three criteria - presence of gastrointestinal symptoms, histologic evidence of eosinophilic infiltration and exclusion of other causes of tissue eosinophilia. The treatment is based on the severity of symptoms. Corticosteroids are the mainstay of therapy, so the usual dose of prednisolone/prednisone is 20-40 mg daily for two weeks with tapering thereafter. In the literature, the use of montelukast and biologic agents have been reported.